Experimental and thermal investigation with optimization on friction stir welding of nylon 6A using Taguchi and microstructural analysis. (October 2021) - Kumar, Gajula Sri Venkata Seshu; Kumar, Anshuman; Rajesh, S; Chekuri, Rama Bhadri Raju; Sundaramurthy, Venkatesa Prabhu
Friction stir welding is an environmentally friendly process of joining due to the non-usage of flux, or any shield gas. Therefore, this article proposes an experimental and thermal investigation with optimization technique for studying the process of FSW on nylon 6A or polycaprolactam polymer composite plates. Specifically, the influence of input operating process parameters such as tool rotational speed (TRS), feed rate, and pitch values on the output response parameters like ultimate tensile strength (UTS), and hardness of welded joints is examined. In addition, L27 orthogonal array of Taguchi approach is employed for the optimization of design experiments of FSW parameters. The experimental setup is carried out with various process parameter combinations like 500, 1000, and 1500 rpm as TRS, 30, 40, and 50 mm as feed rate by varying the pitch values as 1, 2, and 3 mm. Further, the analysis of variance (ANOVA) also employed for finding the significant parameters of input process using the regression analysis equations. Finally, microstructural analysis is used to assess the mixing or dispersing uniformity of composites effectively. The experimental and optimum FSW parameters for maximum UTS are obtained at a feed rate of 30 mm/min, tool pitch of 3 mm, and the TRS of 500 rpm.